The result of effective microorganisms isolated from wastewater and soil (Mongolian Journal of Agricultural Sciences, 2021)
Increasing urbanization and population concentrations are causing environmental problems such as soil and water pollution. In this study, we were present isolation and identification of Streptomyces sp and Rhodobacteria sp. Those effective microorganisms isolated from the wastewater and soil sample of Anand-Khujirt spring resort located in Khujirt soum, Uvurkhangai province in Mongolia. Based on morphological, cultural, and molecular characteristics (16S rDNA sequencing), those strain were identified as Rhodobacter sphaeroides (99% similarity) and Streptomyces cf.griseus (99% similarity). Rhodobacter sphaeroides could be used to reduce heavy metal contamination from soil. Furthermore, Streptomyces cf.griseus is an effective  microorganism, which produces 32 types of biologically active compounds for pharmaceutical or agricultural purposes.Хаягдал ус, хөрснөөс ашигтай бичил биетний цэвэр өсгөвөр ялгасан судалгааны дүнгээсХотжилт, хүн амын төвлөрөл нэмэгдэж байгаа нь хөрс, усны бохирдол зэрэг хүрээлэн буй орчны асуудлуудыг үүсгэж байна. Бид энэхүү судалгааны ажлаар Өвөрхангай аймгийн Хужирт сумын нутагт орших “Ананд-Хужирт” рашаан сувилал,  аялал жуулчлалын баазын хаягдал ус, хөрснөөс ялгасан ашигтай бичил биетний нутгийн омгууд болох Streptomyces sp, Rhodobacteria sp-ийн нуклеотидын дарааллыг Genetyx software програмыг ашиглан боловсруулалт хийн АНУ-ын Биотехнологийн Мэдээллийн Үндэсний Төвийн мэдээллийн сангаас BLAST хайлт хийж хамгийн ойролцоох зүйлийг тодорхойлсон. Rhodobacter sphaeroides (99% ижил нуклеотидтэй)-ийг хүнд металлын бохирдлыг бууруулахад өргөн ашигладаг бол Streptomyces cf.griseus (99% ижил нуклеотидтэй) нь 32 төрлийн биологийн идэвхит нэгдлийг нийлэгжүүлэгч ашигтай бичил биетэн юм.   Түлхүүр үг: Streptomyces spp, Rhodobacteria spp, хаягдал ус, хөрс,